Dampak Ekspansi Perkebunan Sawit Terhadap Kualitas dan Kuantitas Air Tanah: Tinjauan Kritis pada Sifat Fisika Tanah - Powa, M. Raynaldo Sandita (Perkebunan dan Lahan Tropika, 2025)
Indonesia is the world's largest palm oil producer. The expansion of oil palm plantations increased by 10.16% from 2019 to 2023, carried out by both corporations and small-scale farmers in response to the growing demand for palm oil. While this expansion brings economic and social benefits, it also increases the risk of declining groundwater quality and quantity. This study aims to provide a more objective perspective on the impact of oil palm plantation expansion on groundwater quality and quantity through an analysis of soil physical properties. The research method employed is a literature review of books and scientific articles indexed in SINTA and Scopus to ensure data credibility. The data were analyzed using a qualitative descriptive approach. The results indicate that: (1) the decline in soil physical quality directly affects water absorption, increasing the risk of flooding; (2) the high water consumption of oil palm and evapotranspiration leads to reduced groundwater availability; and (3) the use of fertilizers and pesticides in oil palm plantations contributes to water and environmental pollution. To mitigate these negative impacts, strict government oversight is required to ensure that palm oil plantation expansion aligns with green economy principles. Additionally, it is necessary to provide farmers with adequate knowledge, particularly regarding soil physical properties in oil palm plantations, to minimize the adverse effects of oil palm cultivation practices.